2016
DOI: 10.1039/c6ay01779g
|View full text |Cite
|
Sign up to set email alerts
|

Whole blood analysis using microfluidic plasma separation and enzyme-linked immunosorbent assay devices

Abstract: In this study, a microfluidic plasma-separation device that realizes the whole blood analysis of C-reactive protein (CRP) using one drop of blood is developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…There have been multiple reports of standalone microfluidic plasma separation systems. For example, Homsy et al reported the isolation of 12 μL of plasma from 100 μL of whole blood within 7 min . Several other reports described microfluidic devices integrating plasma separation with downstream analyses. For example, Yeh et al separated plasma and carried out on-chip nucleic acid amplification for the detection of HIV-1 RNA and Staphylococcus aureus DNA spiked in whole blood . Another paper described a microfluidic immunoassay for the detection of C-reactive protein performed downstream of plasma separation .…”
Section: Introductionmentioning
confidence: 99%
“…There have been multiple reports of standalone microfluidic plasma separation systems. For example, Homsy et al reported the isolation of 12 μL of plasma from 100 μL of whole blood within 7 min . Several other reports described microfluidic devices integrating plasma separation with downstream analyses. For example, Yeh et al separated plasma and carried out on-chip nucleic acid amplification for the detection of HIV-1 RNA and Staphylococcus aureus DNA spiked in whole blood . Another paper described a microfluidic immunoassay for the detection of C-reactive protein performed downstream of plasma separation .…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, a bio-fluid separation has been performed by centrifugation or chromatography. Recently, there has been technological development integrated with LOC systems, such as microscale-electrophoresis, microfiltration, micropillars, and magnetic microbeads to perform purification to increase detection sensitivity [ 52 ]. Examples of the biofluids for such applications include whole blood and its derivatives plasma and serum.…”
Section: Sample Purification Via Locmentioning
confidence: 99%
“…Quantitative detection of these biomarkers has immensely helped in early diagnosis and treatment of these diseases. In order to accurately diagnose these diseases, sensitive assays and biosensing technologies are required to reliably detect minute quantities of these biomarkers [52][53][54] . Therefore, to test the functionalities of our microarray microfluidic devices, aptamer and antibody-based immunoassays were performed to qualitatively and quantitatively detect IL6 and hCRP.…”
Section: Aptamer-based and Antibody-based Immunoassaysmentioning
confidence: 99%